2007
DOI: 10.1002/ppul.20735
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial cell signaling in response to bacterial pathogens

Abstract: Summary. The airway epithelium represents a primary site for the introduction and deposition of potentially pathogenic microorganisms into the body, through inspired air. The epithelial mucosa is an important component of the innate immune system that recognizes conserved structures in microorganisms and initiates appropriate signaling to recruit and activate phagocytic cells to the airways. This review focuses on how airway epithelial cells sense and respond to the presence of bacterial pathogens. The major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 105 publications
1
55
0
Order By: Relevance
“…In recent years, a variety of in vitro studies have shown that various microbes are capable of activating epithelial cells in a TLR-dependent manner (1,9). Despite the multitude of studies dealing with bacterium-host interaction in vitro, little is known about the function of epithelial TLRs during bacterial colonization of the upper respiratory tract in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a variety of in vitro studies have shown that various microbes are capable of activating epithelial cells in a TLR-dependent manner (1,9). Despite the multitude of studies dealing with bacterium-host interaction in vitro, little is known about the function of epithelial TLRs during bacterial colonization of the upper respiratory tract in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro studies have been performed to gain insight into the immune functions of respiratory epithelial cells (9,10,26,30,37). Respiratory epithelial cells in culture are capable of recognizing microbes through pattern recognition receptors such as Toll-like receptors (TLRs).…”
mentioning
confidence: 99%
“…This pattern of expression is highly correlated with the presence of gross inflammatory lesions (18)(19)(20)(21)(22)(23)(24)(25)(26). Epithelial cells also are known to express chemokines and inflammatory cytokines associated with leukocyte recruitment and activation (27). For example, Mycoplasma genitalium infection of cultured human endocervical epithelial cells revealed the expression of IL-6, IL-7, IL-8, monocyte chemoattractant protein 1 (MCP-1), and granulocyte-macro-phage colony-stimulating factor (GM-CSF) mRNA (28)(29)(30).…”
mentioning
confidence: 99%
“…From the standpoint of antimicrobial resistance, there is the prospect that nitrosative stress/reactive nitrogen could, in vivo, provide a selective pressure for MexEF-OprNproducing multidrug-resistant mutants. Airway epithelial cells are, for example, known to produce NO upon stimulation by bacteria and bacterial products (e.g., lipopolysaccharide [LPS]) (14), and a previously reported in vitro transcriptome study of P. aeruginosa exposed to normal human epithelial cells revealed that mexEF-oprN (and mexS) was substantially upregulated (11). In addition, the observation that several genes identified previously as being members of a MexT regulon are induced in response to nitrosative stress suggests that MexT targets are components of a nitrosative stress response in P. aeruginosa.…”
mentioning
confidence: 99%